"Therapeutic" serum concentration of phenytoin: the influence of seizure type. Issue 3 (March 1984) - Turnbull, D M; Rawlins, M D; Weightman, D; Chadwick, D W
Abstract : Serum phenytoin concentrations were monitored prospectively in 26 patients with previously untreated partial epilepsy, during monotherapy with phenytoin. Only six remained entirely seizure-free, although only four experienced further tonic-clonic seizures. There was no correlation between serum phenytoin concentrations and freedom from partial seizures in those patients in whom such seizures recurred. There did appear to be a correlation between serum phenytoin concentration and freedom from tonic-clonic seizures.